Conservation biology in sub-Saharan Africa - Wilson, John W.; Primack, Richard B., 1950-; Open Book Publishers (Open Book Publishers, 2019)
"Conservation Biology in Sub-Saharan Africa comprehensively explores the challenges and potential solutions to key conservation issues in Sub-Saharan Africa. Easy to read, this lucid and accessible textbook includes fifteen chapters that cover a full range of conservation topics, including threats to biodiversity, environmental laws, and protected areas management, as well as related topics such as sustainability, poverty, and human-wildlife conflict. This rich resource also includes a background discussion of what conservation biology is, a wide range of theoretical approaches to the subject, and concrete examples of conservation practice in specific African contexts. Strategies are outlined to protect biodiversity whilst promoting economic development in the region. Boxes covering specific themes written by scientists who live and work throughout the region are included in each chapter, together with recommended readings and suggested discussion topics. Each chapter also includes an extensive bibliography. Conservation Biology in Sub-Saharan Africa provides the most up-to-date study in the field. It is an essential resource, available on-line without charge, for undergraduate and graduate students, as well as a handy guide for professionals working to stop the rapid loss of biodiversity in Sub-Saharan Africa and elsewhere. Visit the 'Additional Resources' section to find out more about how to download individual chapters and images, upload material to the teaching platform that will be launched in the forthcoming months or join the textbook's discussion forum."--Publisher's website.
Contents -- List of Boxes -- Foreword -- Preface -- Acknowledgements -- List of Acronyms -- Chapter 1. What is Conservation Biology? -- Chapter 2. Introduction to Sub-Saharan Africa -- Chapter 3. What is Biodiversity? -- Chapter 4. Why Should We Protect Biodiversity? -- Chapter 5. The Scramble for Space -- Chapter 6. Our Warming World -- Chapter 7. Pollution, Overharvesting, Invasive Species, and Disease -- Chapter 8. Extinction is Forever -- Chapter 9. Applied Population Biology -- Chapter 10. Conserving Ecosystems -- Chapter 11. Preventing Extinctions -- Chapter 12. Biodiversity and the Law -- Chapter 13. The Importance of Protected Areas -- Chapter 14. Conservation on Unprotected Lands -- Chapter 15. An Agenda for the Future -- Appendix A. Selected Sources of Information -- Appendix B. Selected Environmental Organisations -- Appendix C. Obtaining Conservation Funding -- Appendix D. Environmental Calendar -- Glossary -- Index.
Additional material including teaching resources and updates will be made available on the publisher's website.
Available through Open Book Publishers.
Mode of access: World Wide Web.
Keywords: Conservation biology -- Africa, Sub-Saharan.